Guidelines for industrially-based multiple case studies in software engineering - Verner, J.M.; Sampson, J.; Tosic, V.; Abu Bakar, Nur Azzah; Kitchenham, B.A. (2009)
Without careful methodological guidance, case studies in software engineering are difficult to plan, design and execute.While there are a number of broad guidelines for case study research, there are none that specifically address the needs of a software engineer undertaking multiple case studies in an industrial setting.Through a synthesis of existing best practices in case study research, we provide a set of comprehensive guidelines for conducting multiple case studies in software engineering research.Our guidelines can assist software engineering researchers with all stages of multiple case study research, although in this paper we concentrate on the early phases, such as focusing the case study and detailed plan design.To date, three exploratory research projects found our guidelines very useful.We illustrate our guidelines with examples from one of these projects.